Peranan Pengendalian Internal Persediaan Barang Dagang Dalam Menunjang Efektivitas Pengelolaan Persediaan Barang Dagang Pada PT Rajawali Nusindo Cabang Surabaya - Arifani Salica Putri Winarno; Fajar Syaiful Akbar (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
The rapidly developing business world means that companies must compete by managing their company operations effectively and efficiently to maximize income and maintain business continuity, including PT Rajawali Nusindo Surabaya Branch. Trading companies must be able to manage their inventory as optimally as possible to provide high quality goods needed by customers. Through interview and observation methods, the author analyzes how the role of internal inventory control supports the effectiveness of inventory management. The research results reveal that implementing all five components of internal inventory control can help increase the effectiveness of inventory management. The company has succeeded in implementing structured procedures for procuring, storing and releasing goods. Apart from that, stock taking is carried out regularly to see whether the physical quantities match those on the stock card or system. It is recommended that, so that effectiveness can continue to be produced, it is necessary to carry out regular assessments of the internal control system.